The Spirit of Praise : Music and Worship in Global Pentecostal-Charismatic Christianity - Yong, Amos; Ingalls, Monique Marie (Book collections on Project MUSE., 2015)
"A collection of essays exploring musical sounds and worship practices within Pentecostal Charismatic Christianity. Combines ethnographic case studies with theoretical reflection informed by social science, musicological, religious studies, and theological approaches, resulting in a multidisciplinary analysis of a global phenomenon"--Provided by publisher